Reflections on theories of social optimization and their relevance for future city management in Japan - Yoshiro Higano (Journal of Urban Management, 2013)
The paradigm of laissez-faire economy presumes that economic agents know efficient loci for input-output combinations and rationally act in the market by following their subjective values. Economy is efficiently organized and given dynamic forces to grow at its own risk. As a result, the greatest happiness for a great number is attained. It is difficult to correctly answer the question, why should we consider city management? Of course, the paradigm will not work in a city due to congestion and agglomeration as well as specificity of location. However, it is not sufficient to consider only subsidiary taxes and subsidy systems like Pigouvian prescriptions that lead the market equilibrium to a Pareto Optimum. In a mature economy such as the Japanese economy that faces a long depression under pressure of aging and decreasing population, there are few investable targets as long as it is taken for granted that the paradigm should be maintained. Moreover, in a globalized economy, cities must compete against their rivals. This means not only efficiency of activities in the Pareto sense in the city but a higher absolute level of activity must be realized. In this study, we focused on external costs and benefits that accrue through the activities of economic agents in a city. We argue that activities should be managed and controlled so external benefits are generated to a maximum extent and the activity level of the city is also maximized.
Keywords: 710; city management; socially optimum optimorum; Theories of social benefits; urban future Japan